Melancholia: Art, Science and History in the west (Research, Society and Development, 2019)
The present work lends itself to the objective of understanding the historical and social course of the concept of melancholy and its encounters with the scientific and artistic discourses of the West. For that, a historical survey is presented with an emphasis on the origin of such discourse, in Ancient Greece, and in the romantic period of European literature, where the theme was manifest in a pulsating way. It is a bibliographical review of a qualitative and non-systematic approach in SciELO, PePSIC and Portal Capes books and databases, based on the descriptors History of Melancholy, History of Art, Psychoanalysis and Romanticism. It is concluded that, from its origin until its greater expression, in the romantic poetry, the melancholy was associated with a type of exceptionality, an access to deep ideas and interiorizations, being source of important productions of the culture. Only from the nineteenth century, with the apprehension of the concept by medicine, psychiatry and by psychoanalysis itself, is it inserted in the field of psychopathological frameworks.